Figurative Language Analysis of “CITACINTA CARAKA” Novel by Erisca Febriani - Suzzette Triana Berutu; Tiara K. Pasaribu; Rotua Elfrida Pangaribuan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to describe two main problems, namely: (1) What types of figurative language are found in the novel Cita Cinta Caraka? And (2) What meanings are in the Cita Cinta Caraka Novel? The data in this research is in the form of speech in the novel Cita Cinta Caraka by Erisca Febriani, which contains a figurative language style. This type of research is descriptive qualitative. This novel is analyzed using Keraf's theory. This novel contains 107 data. After examining the figurative language data in the novel Cita Cinta Caraka, it is known that there are 28 personifications, 10 hyperboles, 14 similes, 15 metaphors, 21 ironies, 6 litotes, 9 metonymies, 1 eponym, 2 antonyms, and 1 euphemism. Based on the analysis findings, personification-figurative language is the most dominant in the novel. The author uses personification to explain the meaning or message of each character and the author's intentions, as well as expressing the characters' emotions, making the story more exciting and entertaining, and being able to make readers more quickly understand the meaning of the words of each character in the novel. It can be concluded that figurative language has an important role in this novel. Therefore, the author uses many figurative sentences in this novel. The use of figurative language makes the novel more interesting to read and helps readers imagine the story and the characters based on the illustrations that the author has given in the story.